DETEKSI VIRUS JAPANESE ENCEPHALITIS PADA MANUSIA DAN VEKTOR DI KABUPATEN TULUNGAGUNG, JAWA TIMUR - Nova Pramestuti; Tri Wijayanti; Dyah Widiastuti; Tri Isnani (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2020)
Japanese encephalitis is a zoonotic disease transmitted by mosquitoes with pigs as the main reservoir. A small percentage of infected people experience acute encephalitis syndrome, with one in four cases fatal. Recently, the existence of a growing pig population has the potential to increase the risk of JE transmission in Tulung Agung, East Java, Indonesia. The purpose of this study was to detect JE infection in humans and mosquitoes in Tulungagung Regency. A cross-sectional design was conducted from March to October 2016. Human blood screening was carried out in six hospitals in Tulungagung and the mosquitos survey was carried out using human landing collection, resting collection, and light trap around the pig farms in Kaliwungu District. Detection of JE infection was carried out by indirect immuno-linked immunosorbent assay (ELISA) testing of IgM/IgG in human serum samples and Polymerase Chain Reaction (RT-PCR). Transcription reaction in mosquitoes. The ELISA test showed that one of 19 human serum samples was confirmed positive with JE specific IgG. The result of the mosquito survey showed that Anopheles vagus was predominantly collected in Kaliwungu village, while Culex quinquefasciatus was was predominantly species collected in Pulosari Village. The analyses using molecular assays showed that all captured mosquitoes were negative Javanese encephalitis virus (JEV). Abstrak Japanese Encephalitis (JE) merupakan penyakit zoonotik yang ditularkan oleh nyamuk dengan reservoir utama babi. Sebagian kecil orang yang terinfeksi mengalami radang otak (ensefalitis), sekitar satu dari empat kasus berakibat fatal. Peningkatan populasi ternak babi di Kabupaten Tulungagung berpotensi menyebarkan virus JE. Tujuan penelitian untuk mendeteksi infeksi JE pada manusia dan nyamuk di Kabupaten Tulungagung. Penelitian dilakukan pada Bulan Maret-Oktober tahun 2016 dengan desain studi potong lintang. Survey darah manusia dilakukan pada enam rumah sakit di Kabupaten Tulungagung. Survei nyamuk dilakukan satu kali dengan metode umpan badan manusia dan perangkap cahaya, serta penangkapan nyamuk istirahat di sekitar peternakan babi di Kecamatan Kaliwungu. Deteksi infeksi JE dilakukan dengan pemeriksaan Indirect Enzyme-Linked Immunosorbent Assay (ELISA) IgM/IgG pada sampel serum manusia dan Reverse Transcription Polymerase Chain Reaction (RT-PCR) pada nyamuk. Hasil pemeriksaan laboratorium terhadap antibodi IgM/IgG JE menunjukkan satu kasus positif IgG JE dari 19 sampel serum manusia yang diperiksa. Spesies nyamuk yang tertangkap di Desa Kaliwungu didominasi Anopheles vagus, sedangkan di Desa Pulosari didominasi Culex quinquefasciatus. Hasil pemeriksaan RT-PCR terhadap semua sampel nyamuk yang tertangkap menunjukkan negatif virus JE. Satu pasien ditemukan positif antibodi IgG Japanese encephalitis di Kabupaten Tulungagung.